Tugume, Hassan Lubowa - The Prospects of Integrating Traditional Religion and Orthodox Psychiatric Healing Methods Among the Baganda of Uganda. (East African Journal of Traditions, Culture and Religion, 2021)
The main objective of this study is to analyse the possibility of integrating traditional psychiatric healing methods among the Baganda into Orthodox healing practices. The debate was influenced by the resistance of some ailments to the orthodox medication and the proven efficacy of traditional healing processes in the treatment of some complications. This paper has singled out psychiatric complications. In Uganda, the ambience of psychiatric victims on the streets of Kampala and towns has raised concern about the efficiency of the psychiatric hospital at Butabika in Kampala. The primary data were obtained through interviews and questionnaires through a survey in five counties of Buganda kingdom. On the other hand, secondary data were obtained through a review and synthesis of relevant literature on Buganda, psychiatric healing, religion and African culture. The empirical analysis was done through descriptive analysis using analytical and critical tools. This paper established that the need for alternative approaches to psychiatric cases led to new interest in traditional healing which has shown some positive responses. Consequently, traditional practitioners under their association of native healers have availed themselves the opportunity of this debate to call for recognition as partners in the provision of effective and affordable health care. This paper explored the traditional psychiatric healing process in Buganda, Uganda by analysing the various concepts, perspectives and dimensions and argued for the integration of traditional methods with modern ones.